2005
DOI: 10.1111/j.1944-9720.2005.tb02452.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Speaking Skills Through Instruction in Oral Classroom Participation

Abstract: Studies in language learning have addressed the necessity of classroom interaction or students' oral participation in class. However, getting students to respond in a language classroom—especially a foreign language class—is a problem that most language teachers face. This article suggests remedies to language learners' reticence, using Taiwanese students as participants. Instruction about classroom participation was provided to students in the experimental group to see whether this treatment can (a) increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 26 publications
2
52
0
Order By: Relevance
“…In Swain & Lapkin (1998) the communicative undertakings which involved learners significantly improved student learning. In addition, Tsou (2005) conducted an experimental study through questionnaires, tests and participation turns in a Taiwanese university. Both qualitative and quantitative data showed that engagement and interaction through communicative activities improved the treatment group's language skills especially speaking skills.…”
Section: Empirical Evidencementioning
confidence: 99%
“…In Swain & Lapkin (1998) the communicative undertakings which involved learners significantly improved student learning. In addition, Tsou (2005) conducted an experimental study through questionnaires, tests and participation turns in a Taiwanese university. Both qualitative and quantitative data showed that engagement and interaction through communicative activities improved the treatment group's language skills especially speaking skills.…”
Section: Empirical Evidencementioning
confidence: 99%
“…However, there are limited opportunities to speak English or listen to a speech in English in countries where it is not an official language (Hwang et al, in press;Hwang & Shadiev, 2014). According to Cheon (2003) and Tsou (2005), in countries of the Asia-Pacific region such as South Korea, Japan, and Taiwan, reading and writing are emphasized far more than listening and speaking, particularly in elementary schools. Several factors lead to this lack of oral and listening practice, including the absence of an English context to stimulate speaking and listening, the instructors' lack of confidence, or the deficiency of good spoken English examples, and excessive dependence upon traditional teaching techniques.…”
Section: Introductionmentioning
confidence: 99%
“…As Krupa-Kwiatkowski (1998, p.133) claimed, 'interaction involves participation, personal engagement, and the taking of initiative in some way, activities that in turn are hypothesized to trigger cognitive processes conducive to language learning'. Since oral participation is the most observable behavior, much research has focused on it and its relationship with students' English proficiency or performance (Ely, 1986;Liu & Jackson, 2008;Spada, 1986;Swain, 1985;Tsou, 2005).…”
Section: Language Class Risk-taking and Sociabilitymentioning
confidence: 99%